(e) in Normandy: The sociolinguistics, phonology and phonetics of the Loi de Position. Issue 1 (8th August 2018) - HALL, DAMIEN
ABSTRACT: This article uses the pronunciation of stressed Intonational Phrase-final /ε/ and /e/ in two communities in Normandy, France, to illustrate the convergence of two sociolinguistic processes on the same phonological result: increasing application of the Loi de Position . In both communities (one rural and further from Paris, one urban and closer to Paris), there is now no consistent community-wide phonetic distinction between the two phonemes in that environment. It is suggested that the Loi de Position is already widely applied in the rural site, but speakers are still conscious of the formal norm whereby it is not applied; for the urban site, apparent-time changes for this variable reflect changes in Parisian speech. The theoretical implications of the study concerning speakers' organisation of their vowel-space, and concerning the increasing application of the Loi de Position in the French of France, are examined. These conclusions are reached by per-speaker analysis of F1 and F2 separately from each other (rare in French linguistics). As a measure of community cohesion, the article introduces to linguistics the coefficient of variation (more common in biology and medicine).